Variations in the composition and frequency of celiac disease epitopes among synthetic wheat lines - Rahman Ebrahimzadegan; Ghader Mirzaghaderi (Frontiers in Plant Science)
Bread wheat serves as an important staple crop in the human diet, largely because of the physicochemical properties of its dough and its protein content. Gluten is the main and complex component of wheat proteins. Despite the significant importance in breadmaking properties, wheat gluten contains some immunogenic peptides capable of triggering a T cell reaction in celiac disease (CD) patients, leading to inflammation in the small intestine. Among gluten proteins, α-gliadins are the most immunogenic components because they possess the primary T-cell stimulating epitopes (DQ2.5-Glia-α1, DQ2.5-Glia-α2, and DQ2.5-Glia-α3), which are primarily located on the D subgenome. Developing new wheat varieties by integrating the D subgenome from various sources is not only useful for introducing low immunogenic gluten, but it can also circumvent the challenging policies arising from the manipulation of wheat genome through transgenic approaches. Here, we performed RNA amplicon sequencing of the most toxic region of alpha-gliadins to analyze the content and composition of CD-related alpha-gliadin epitopes across eight synthetic wheat lines developed from crosses between durum wheat and different Aegilops species containing the D-genome (Ae. tauschii, Ae. crassa, and Ae. ventricosa). By searching the previously identified 121 epitopes and those with one mismatch in our amplicons, we found 54 different α-gliadins epitopes across our genotypes, four of which were new variants. The canonical epitopes were present in all lines, although their expression patterns varied. The occurrence of DQ2.5-Glia-α1a and DQ2.5-Glia-α3 was higher than that of DQ2.5-Glia-α2 and DQ2.5-Glia-α1b across all genotypes. Since a higher quantity of toxic alpha-gliadin epitopes is associated with increased immunogenicity in individuals susceptible to celiac disease, we measured the frequency of the most toxic alpha-gliadin epitopes among different synthetic lines to estimate the overall immunogenic load of our lines. Generally, the immunogenic load of lines with the D-genome originating from Ae. crassa was much lower than those with the D-genome from Ae. tauschii. In this way, the Ae. tauschii derived lines 5 and 6 contained higher levels of toxic alpha-gliadin epitopes, while lines 3, 4, and 7 (derived from Ae. crassa) contained the lowest levels of toxic peptides. We conclude that replacing the bread wheat D-genome with that of the Ae. crassa may help lower the gluten immunogenicity in the deriving synthetic wheat lines.